Performance Under Stress: An Eye-Tracking Investigation of the Iowa Gambling Task (IGT) - Simonovic, Boban; Stupple, Edward J. N.; Gale, Maggie; Sheffield, David (Frontiers in Behavioral Neuroscience, 2018)
Stress impedes risky decision-making. Effects of stress induced by anticipated public speaking on the Iowa Gambling Task (IGT) were examined in a sample of 76 participants. Inspection time was recorded with an eye-tracker during the IGT. Conscious awareness of deck contingencies was also assessed. Additionally, the extended version of Cognitive Reflection Task (CRT) examined the relationship between reflective thinking and IGT performance. The stress manipulation was effective as blood pressure was increased. Stressed participants were slower to avoid the disadvantageous decks and performed worse overall. The inspection time for disadvantageous decks was greater in the stress condition than the control condition. such that stress inhibited the ability to disengage from negative selections. Conversely. greater inspection time for advantageous decks was observed early in the task, for the control condition. This indicated slower development of conscious awareness of the deck contingencies. Differences in conscious awareness of deck contingencies emerged in Block two and were consistently poorer in the stress condition. Thus, explicit cognitive processes play a significant role during the preliminary phase of IGT performance. Path analysis showed that stress reduced IGT performance by impeding reflective thinking and conscious awareness. It was concluded that stress impedes reflective thinking, attentional disengagement from poorer decks, and the development of conscious knowledge that consequently interferes with performance on the IGT.